2002
DOI: 10.1063/1.1477282
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Raman scattering measurements of strains in ZnS epilayers grown on GaP

Abstract: The relaxation of strain in the ZnS epilayers grown on (100) GaP was investigated with resonant Raman scattering measurement. The single LO phonon resonant Raman shift and the intensity increased but the full width at half maximum decreased with the increasing ZnS epilayer thickness. These were attributed to the relaxation of the biaxial tensile strain with the generating misfit dislocations. Finally, the critical thickness of ZnS/GaP epilayer was found to be around 35 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The Resonance Raman scattering is highly sensitive and can detect the weak surface phonon signal. 40,44 Luo et al 40 also observed the surface optical phonon scattering from hollow ZnS microspheres, and the defects on the surface of the hollow ZnS microspheres are considered as the origin of the SO modes. Therefore, the SO modes may be attributed to the surface and interfacial defects of ZnS generated during heat treatment processes.…”
Section: Structure and Morphology Of Zns Nanocrystalsmentioning
confidence: 99%
“…The Resonance Raman scattering is highly sensitive and can detect the weak surface phonon signal. 40,44 Luo et al 40 also observed the surface optical phonon scattering from hollow ZnS microspheres, and the defects on the surface of the hollow ZnS microspheres are considered as the origin of the SO modes. Therefore, the SO modes may be attributed to the surface and interfacial defects of ZnS generated during heat treatment processes.…”
Section: Structure and Morphology Of Zns Nanocrystalsmentioning
confidence: 99%
“…First observation is Sample A formation SnSe phase peaks located at 186 cm −1 [28]. It displays SnSe phase formation when the temperature at 673 K. And there are Cu 2 SnSe 3 and Cu 2 SnS 3 are located at 248 and 336 cm −1 [29,30], also found ZnS phase is located at 353 cm −1 [31]. Meanwhile, CZTSSe phase is formed.…”
Section: Phase Change Mechanisms Of Cztsse Filmmentioning
confidence: 89%
“…Among a wide bandgap of 3.7 eV and subsequent low absorption in visible wavelengths, it has several applications, from filter and lens materials to UV photodiodes and other compound semiconducting devices [1][2][3][4][5][6]. ZnS is one of the most widely used materials for window layer heterojunction photovoltaic solar cells.…”
Section: Introductionmentioning
confidence: 99%